Enhancing Quality of Basic Level Education through Demonstration Method (Triyuga Academic Journal, 2024)
The article, ‘Enhancing Basic Level Quality Education Through Demonstration Method’ explores the different aspects of demonstration method. The use of suitable and effective teaching methods plays a crucial role in shaping the learning experiences of basic school students. This study aims to explore the implementation of the demonstration method in basic education. Among various teaching methods in the field of education, the demonstration method is notable for engaging students through experiential learning. This article employs a qualitative research design, incorporating interviews with teachers, focus group discussions with students, and literature reviews to gather data. Empirical evidence is presented to support the findings, offering insights into the application of the demonstration method in diverse educational contexts. The study reveals that the demonstration method enhances students' learning outcomes when utilized in classroom teaching. It ensures that all students have the opportunity to understand the material presented by the teacher. This method is particularly effective for subjects that involve practical skills and processes, such as science experiments and mathematical problem-solving.